2021
DOI: 10.1186/s13018-021-02230-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers of osteoarthritis: early diagnosis in susceptible Pakistani population

Abstract: Background and aim Osteoarthritis (OA) is a multiple factorial disease with unidentified specific markers. The alternate method such as biochemical and genetic markers for the diagnosis of osteoarthritis is an undeniable need of the current era. In the present study, we aimed to investigate the association of interleukin-6 (IL-6)(IL-6-174G/C), transforming growth factor-β1 (TGF-beta1-29C/T), and calmodulin 1 gene-16C/T (CALM1-16C/T) polymorphism in clinically definite Pakistani OA patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…(Al-Arfaj, 2002). Badshah et al, 2021, also reported that compared to the male population, women are more likely than men to have OA. (Badshah et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…(Al-Arfaj, 2002). Badshah et al, 2021, also reported that compared to the male population, women are more likely than men to have OA. (Badshah et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The results analyzed based on gender and age group shows difference in OD and relative risk in male and female and suggest that a male with allele AA may have at higher risk compared to female, but no clear results were achieved from analysis based on age group because of the sample size. The association of polymorphism with genetic disease gave us an idea about susceptibility and can also be used for early diagnosis as the study of the osteoarthritis in Pakistani population revealed that polymorphisms in IL-6, TGF-beta-1 and CALM 1 genes were associated with the disease [ 36 ]. It has been established that high ALT) levels are linked with HCV induced HCC) and can lead to the disease rapidly [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have confirmed that genetic factors play a major role in the pathogenesis of osteoarthritis. Studies based on the family history also confirmed that OA has hereditary susceptibility [78,79]. The main mechanisms leading to OA were chemical modification of DNA, such as methylation, posttranslational modification of histones, and regulation of noncoding RNA.…”
Section: Genetic Factorsmentioning
confidence: 92%